Increasing Literature And Sharia Financial Management Through The One BMT Housing Area Program In Banguntapan District Bantul In Yogyakarta - Ayif Fathur Rahman; Yuli Utami (ABDIMAS: Jurnal Pengabdian Masyarakat, 2021)
The target of this PKM program is economically productive communities, namely people in housing in Banguntapan sub-district who have just established BMT covering aspects of marketing/socialization and management and accounting information systems (small businesses). The aim of the program is to develop an economically independent community with high literacy on syar'i transactions. Business partners in this program are BMTs that have just been established with a residential mosque base, namely BMT Sakinah, BMT Al-Anbiya and BMT Al-Huda. The problems faced by the three partners are: 1) Lack of competence and management in managing BMT, 2) Lack of legality, 3) Lack of Islamic financial literacy, so that BMT members still do not understand the function of BMT. As for the method of devotionare general lectures, short courses, tutorials and simulations. Materials that are focused on include the management and members of BMT: 1) Socialization of Transaction Contract applications legalized by the National Sharia Board, 2) Consolidating the understanding and application of Management Information Systems and Accounting Information Systems for BMT, for approximately eight months. The result of this dedicationis special assistance and provides BMT financial system software so that the BMT, BMT Sakinah (Puri Sakinah 2 Housing), BMT Al-Anbiya (Pesona Banguntapan Kotagede Housing) and BMT Al-Huda (Graha Banguntapan Housing) can manage accountably, professional and transparent. This program is expected to be able to facilitate the development of partner businesses so that they are able to provide a multiplier effect for housing-based BMTs and other newly established mosques.